'A most picturesque mass of rags': Romani costume and undress in nineteenth-century travel descriptions of Hungary. (20th October 2019) - Davis, Sacha E.
ABSTRACT: Davis examines descriptions of Romani costume in travel narratives written by predominantly British writers visiting Hungary, believed to be the site of especially 'pure' Romani culture, during the long nineteenth century. Travel descriptions provided key sources of information on the peoples of East Europe, for the British public, authors of popular fiction and Gipsiologists alike. However, most travellers spent little time with Roma. Consequently, they supplemented descriptions of surface details, such as Romani costume, with information from local informants and Gipsiologists' texts. Following these sources, travellers ethnologized Romani costume, demonstrating Orientalism and tropes of poverty, indolence, licentiousness, neglect, vanity and essentialism. In the process, travel writers reinforced and disseminated the 'pure Romany' stereotype to wider audiences.